Global Research Trends on Augmented Reality in Science Education: A Bibliometric Analysis (2020–2025) - Rahmia Tulljanah Rahmi; Wahyuni Mulia Helmi; Rahmatia Wulan Dari; Riri Marfilinda; Meria Ultra Gusteti (Jurnal Penelitian Pendidikan IPA, 2026)
This study uses a bibliometric approach to analyze global research trends regarding the use of Augmented Reality (AR) in science education in the period 2020–2025. Data was obtained from the Scopus database as of July 16, 2025 using the keywords "augmented reality" and "science" searched for titles, abstracts, and author keywords, resulting in 223 initial documents. After going through a systematic screening process based on inclusion and exclusion criteria, including publication type, peer-review status, language, and time span, 102 articles were obtained that were worthy of further analysis. The analysis was carried out using VOSviewer through the stages of data extraction, cleaning, network construction, and visualization. The results of the study show that the study of AR in science education has increased significantly, especially in the 2020–2024 period with a peak in 2024. The largest contributions of publications come from Turkey, Indonesia, the United States, Malaysia, Taiwan, and China, reflecting the global spread of the field. The main journals that are the publication sites include Computers & Education, Education and Information Technologies, and Interactive Learning Environments. The co-word analysis revealed three dominant themes, namely: (1) the effectiveness of AR in improving student learning outcomes, (2) the challenges and development of AR implementation in education, and (3) the role of teachers, student involvement, and evaluation practices in AR-based learning. Meanwhile, the analysis of the co-authorship network showed that there were several clusters of cross-institutional and cross-country collaboration with a number of key authors acting as liaison. In conclusion, AR is not only seen as a technological innovation, but also as a pedagogical strategy that is able to increase motivation, understanding of concepts, and learning interactions in science education.